Long-Term Inactivation Study of Three Enteroviruses in Artificial Surface and Groundwaters, Using PCR and Cell Culture - de Roda Husman, A. M. (American Society for Microbiology (ASM), 2009)
Since the transmission of pathogenic viruses via water is indistinguishable from the transmission via other routes and since the levels in drinking water, although significant for health, may be too low for detection, quantitative viral risk assessment is a useful tool for assessing disease risk due to consumption of drinking water. Quantitative viral risk assessment requires information concerning the ability of viruses detected in drinking water to infect their host. To obtain insight into the infectivity of viruses in relation to the presence of virus genomes, inactivation of three different enteroviruses in artificial ground and surface waters under different controlled pH, temperature, and salt conditions was studied by using both PCR and cell culture over time. In salt-peptone medium, the estimated ratio of RNA genomes to infectious poliovirus 1 in freshly prepared suspensions was about 10(0). At 4°C this ratio was 10(3) after 600 days, and at 22°C it was 10(4) after 200 days. For poliovirus 1 and 2 the RNA/infectious virus ratio was higher in artificial groundwater than in artificial surface water, but this was not the case for coxsackievirus B4. When molecular detection is used for virus enumeration, it is important that the fraction of infectious virus (based on all virus genomes detected) decays with time, especially at temperatures near 22°C.